PENGARUH PETRISSAGE BACK MASSAGE KOMBINASI ESSENTIAL OIL LAVENDER TERHADAP SKALA NYERI KALA 1 FASE AKTIF DI DESA KARANGSUKO - Andikasari, Eprilia Redita; Wijayanti, Tut Rayani Aksohini (FORUM ILMIAH KESEHATAN, 2025)
Labor pain during the active phase of the first stage of labor is an intense experience for laboring mothers. Petrissage back massage combined with lavender essential oil can be an effective non-pharmacological pain management alternative. The purpose of this study was to analyze the effectiveness of petrissage back massage combined with lavender essential oil in reducing pain levels in laboring mothers during the active phase of the first stage. This was a pre-experimental study with a one-group pretest and posttest design, involving 25 laboring mothers. The intervention was petrissage back massage combined with lavender essential oil for 15 minutes. Pain levels were measured using the Numeric Rating Scale (NRS) before and after the intervention. Pain levels were then compared using the Wilcoxon test. The analysis showed that the majority of pain scores in the pre-intervention phase were 8 (64%) and in the post-intervention phase were 7 (56%). The Wilcoxon test showed a p-value of <0.001, with a Z-value of -4.320. The study concluded that petrissage back massage combined with lavender essential oil is effective in reducing pain levels in the active phase of the first stage of labor.Keywords: petrissage massage; lavender essential oil; labor pain; active phase of first stage of laborABSTRAK Nyeri persalinan kala 1 fase aktif merupakan pengalaman yang intens bagi ibu bersalin. Petrissage back massage kombinasi essential oil lavender dapat menjadi alternatif manajemen nyeri non-farmakologis yang efektif. Tujuan penelitian ini adalah menganalisis efektivitas petrissage back massage kombinasi essential oil lavender untuk menurunkan tingkat nyeri pada ibu bersalin kala 1 fase aktif. Penelitian ini merupakan studi pra-eksperimental dengan rancangan one-group pretest and posttest, yang melibatkan 25 ibu bersalin. Intervensi yang dilakukan adalah petrissage back massage kombinasi essential oil lavender selama 15 menit. Tingkat nyeri diukur menggunakan Numeric Rating Scale (NRS) pada fase sebelum dan sesudah intervensi. Selanjutnya tingkat nyeri dibandingkan dengan uji Wilcoxon. Hasil analisis menunjukkan bahwa mayoritas skor tingkat nyeri pada fase sebelum intervensi adalah 8 (64%) dan pada fase sesudah intervensi adalah 7 (56%). Uji Wilcoxon menunjukkan nilai p adalah <0,001, dengan nilai Z adalah -4,320. Sebagai kesimpulan, dinyatakan bahwa petrissage back massage kombinasi essential oil lavender efektif untuk menurunkan tingkat nyeri kala 1 fase aktif persalinan.Kata kunci: petrissage massage; essential oil lavender; nyeri persalinan; kala 1 fase aktif